2020
DOI: 10.1042/bsr20192429
|View full text |Cite
|
Sign up to set email alerts
|

APC gene 3′UTR SNPs and interactions with environmental factors are correlated with risk of colorectal cancer in Chinese Han population

Abstract: Objective: To study the correlation between adenomatous polyposis coli (APC) gene 3′ untranslated region (UTR) single nucleotide polymorphisms (SNPs) and their interactions with environmental factors and the risk of colorectal cancer (CRC) in a Chinese Han population. Methods: Genotypes of APC gene 3′UTR rs1804197, rs41116, rs448475, and rs397768 loci in 340 Chinese Han patients with CRC and 340 healthy controls were analyzed. All patients with CRC were analyzed for progression-free survival (PF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…In recent years, with an in-depth understanding of the pathogenesis of pancreatic cancer, it has been recognized that the development of pancreatic cancer is not only related to genetic factors such as gene mutations but is also closely related to epigenetic abnormalities ( 30 ). Moreover, it has also been found that the APC gene, as an cancer suppressor gene, is rarely mutated, and the mechanisms causing the loss of function of this gene include loss of heterozygosity and promoter methylation, in which the “silencing” of gene function caused by promoter methylation is the main cause of the down-regulated gene expression ( 31 , 32 ). Currently, APC gene promoter hypermethylation as well as gene transcription and expression deletion have been observed in colorectal ( 33 ), esophageal ( 34 ), gastric ( 35 ), pancreatic ( 36 ), hepatocellular ( 37 ), breast ( 38 ), endometrial ( 39 ), and lung ( 40 ) cancers.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, with an in-depth understanding of the pathogenesis of pancreatic cancer, it has been recognized that the development of pancreatic cancer is not only related to genetic factors such as gene mutations but is also closely related to epigenetic abnormalities ( 30 ). Moreover, it has also been found that the APC gene, as an cancer suppressor gene, is rarely mutated, and the mechanisms causing the loss of function of this gene include loss of heterozygosity and promoter methylation, in which the “silencing” of gene function caused by promoter methylation is the main cause of the down-regulated gene expression ( 31 , 32 ). Currently, APC gene promoter hypermethylation as well as gene transcription and expression deletion have been observed in colorectal ( 33 ), esophageal ( 34 ), gastric ( 35 ), pancreatic ( 36 ), hepatocellular ( 37 ), breast ( 38 ), endometrial ( 39 ), and lung ( 40 ) cancers.…”
Section: Introductionmentioning
confidence: 99%